Surveillance for variant CJD: should more children with neurodegenerative diseases have autopsies?. Issue 4 (18th October 2018) - Verity, Christopher; Winstone, Anne Marie; Will, Robert; Powell, Alison; Baxter, Peter; de Sousa, Carlos; Gissen, Paul; Kurian, Manju; Livingston, John; McFarland, Robert; Pal, Suvankar; Pike, Michael; et al.
Abstract : Objectives: To report investigations performed in children with progressive neurodegenerative diseases reported to this UK study. Design: Since 1997 paediatric surveillance for variant Creutzfeldt-Jakob disease (vCJD) has been performed by identifying children aged less than 16 years with progressive intellectual and neurological deterioration (PIND) and searching for vCJD among them. Setting: The PIND Study obtains case details from paediatricians who notify via the British Paediatric Surveillance Unit. Participants: Between May 1997 and October 2017, a total of 2050 cases meeting PIND criteria had been notified and investigated. Results: Six children had vCJD. 1819 children had other diagnoses, made in 12 cases by antemortem brain biopsy and in 15 by postmortem investigations. 225 children were undiagnosed: only 3 had antemortem brain biopsies and only 14 of the 108 who died were known to have had autopsies; postmortem neuropathological studies were carried out in just 10% (11/108) and only two had prion protein staining of brain tissue. Of the undiagnosed cases 43% were known to come from Asian British families. Conclusions: Most of the notified children had a diagnosis other than vCJD to explain their neurological deterioration. None of the undiagnosed cases had the clinical phenotype of vCJD but brain tissue was rarely studied to exclude vCJD. Clinical surveillance via the PIND Study remains the only practical means of searching for vCJD in UK children.